2017
DOI: 10.5505/tjtes.2017.78027
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic rupture: a single-institution experience and review of the literature

Abstract: BACKGROUND: Diaphragmatic rupture (DR) is a rare and potentially life-threatening event caused by trauma or spontaneously. DR occasionally occurs several months after the injury. Chest X-ray and computed tomography are the most effective diagnostic methods. Delay in DR diagnosis occurs frequently. This study aimed to examine and improve our understanding of the etiology, clinical presentation, and management of DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
3
15
1
1
Order By: Relevance
“…However, if the bowel is compromised with signs of gross contamination, the patient may require longterm antibiotics, an extensive washout, and possible bowel resection and colostomy, as reported by Corbellini et al In their retrospective study analyzing 14 patients with diaphragmatic rupture, they report a case with diaphragmatic rupture and bowel perforation which required a transverse colon resection and colostomy in addition to the standard reduction and primary repair. The authors reported 3 patients (27%) with postoperative pulmonary-related complications, which were successfully treated conservatively, as in our case [7].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, if the bowel is compromised with signs of gross contamination, the patient may require longterm antibiotics, an extensive washout, and possible bowel resection and colostomy, as reported by Corbellini et al In their retrospective study analyzing 14 patients with diaphragmatic rupture, they report a case with diaphragmatic rupture and bowel perforation which required a transverse colon resection and colostomy in addition to the standard reduction and primary repair. The authors reported 3 patients (27%) with postoperative pulmonary-related complications, which were successfully treated conservatively, as in our case [7].…”
Section: Discussionsupporting
confidence: 52%
“…In a recent retrospective study analyzing 14 patients diagnosed with diaphragmatic rupture, Corbellini et al found 57% of patients were diagnosed preoperatively, while the remaining 43% were diagnosed intraoperatively. Investigators found chest radiographs and CT scans to be diagnostic in 50% and 60% of cases, respectively [7]. When there is a high degree of suspicion despite "negative" diagnostic imaging, the clinician should consider direct visualization by laparoscopy or thoracoscopy, which can exclude or confirm the existence of a diaphragmatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Since diaphragmatic injuries are quite uncommon in trauma, with a reported incidence in literature between 0.8% and 8% [1], the true incidence of abdominal organ herniation is unknown, also because many cases remain undiagnosed. The blunt vs. penetrating trauma ratio is widely variable geographically [[1], [2], [3]]. Male people, especially aging from 30 to 45 y.o.…”
Section: Introductionmentioning
confidence: 99%
“…In trauma, this is often performed through a laparotomy due to likely abdominal visceral injury; however, for nontraumatic rupture thoracotomy is the favored approach. Usually the diaphragm can be repaired directly with sutures; however, if the defect is large, or quality of tissue poor, a polypropylene mesh or Goretex patch can be used to reduce tension on the repair . Recently, there are reports of repair being performed by VATS …”
Section: Discussionmentioning
confidence: 99%